Peripartum cardiomyopathy in Turkey: Experience of three tertiary centres. (3rd July 2016) - Akil, Mehmet Ata; Bilik, Mehmet Zihni; Yildiz, Abdulkadir; Acet, Halit; Ertas, Faruk; Simsek, Hakki; Polat, Nihat; Zengin, Halit; Akilli, Rabia; Agacayak, Elif; Kayan, Fethullah; Ozdemir, Mahmut; et al.
Abstract : We conducted this study to determine demographic details, and clinical presentations in patients with peripartum cardiomyopathy (PPCMP) of Turkish origin. The study population consisted of 58 patients with PPCMP treated at 3 major hospitals in Turkey, retrospectively. In this study, demographic details and initial echocardiographic data were recorded and long-term clinical status was evaluated. The mean age for the patient cohort was 31.47 ± 6.31 years. Thirty-eight patients (73.1%) were multigravida and seven patients had multifetal pregnancy (13.7%). The mean follow-up left ventricular (LV) ejection fraction increased from 31 ± 7 to 38 ± 19. A minority of patients were defined as improvers according to our pre-specified criteria. The average survival period after diagnosis of PPCMP was 20.66 ± 14.44 months. Initial values for LV end-diastolic diameter and urea were higher in the deceased patients compared with the surviving patients, respectively. Twenty-eight (48%) patients with PPCMP showed improvement in the follow-up period. Of the 58 PPCMP patients, 9 (15%) died during a mean follow-up of 32 ± 22 months.